Factors Affecting Knowledge Sharing Intention of Expert in Group of Faculty Member Telkom Corporate University - Tirana, Rezka Andria; Tjakraatmadja, Jann Hidajat (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. Telkom CorpU has expert who have been recognized as employees with particular skill and experience. But based on data, some expert feel knowledge sharing is not already become culture among them. Indeed, knowledge sharing is a vital part from knowledge management processes and the key success in KM implementation. The low level of knowledge sharing and the fact of that most senior experts will retire in two years make the management feel anxious. For this reason, management tries to find ways to improve expert knowledge sharing behavior so in the future there will be no such anxiety. Theory of Planned Behavior is a theory about factors that influence individual intention toward particular behavior. The theory states that there are three factors that influence individual intention to particular behavior, namely attitude, subjective norm and perceived behavioral control. But for intention of expert in conducting knowledge sharing, the factors that influence significantly are perceived behavioral control only. Other factors such as attitude and subjective norms only potentially affecting expert intentions in carrying out knowledge sharing.Keywords:Â Attitude, intention, knowledge sharing, subjective norm, perceived behavioral control